Optimization of chaotic bioprinting to produce reinforced multichannel hydrogel fibers for the maturation of skeletal muscle tissue under agitation - Cavero Arrivasplata, Andrea Cristina (2024)
Chaotic bioprinting enables the fabrication of microstructured hydrogel fibers with co-extruding permanent and fugitive inks using a kenics static mixer (KSM) printhead. However, these fibers degrade completely after 7 days of static culture. Survival of hydrogel constructs for prolonged periods is critical for tissue maturation. Therefore, in this project, chaotic bioprinting was optimized to reinforce multichannel hollow fibers, thereby extending the culture time to enable skeletal muscle tissue maturation. A KSM printhead equipped with eight inlets and two mixing elements was used to print hydrogel fibers with three materials: a bioink suitable to load cells, a sacrificial material to create hollow channels, and a structural material to provide mechanical stability (without cells). Each bioink layer was placed 62.5 µm apart from a hollow channel. Furthermore, the optimal ratio for each material was determined to enhance structural stability. The tensile test and degradation analysis indicated that the hydrogel fibers composed of 37.5% of the structural ink, 37.5% of the bioink and 25% of the sacrificial ink exhibited sufficient strength (elastic modulus = 12, 8 kPa) to conserve more than 75% of their mass after 72 h of continuous agitation in a rocking bioreactor. In contrast, the fibers containing no reinforcing ink entirely degraded in the same period or earlier. The bioprinting experiments also showed that mouse myoblasts adhering to the reinforced hollow fibers exhibited greater cell viability (95%) than myoblasts on reinforced solid filaments during 14 days of static culture. In the future, these reinforced multichannel fibers could mature musculoskeletal tissue with culturing under continuous agitation.